Superb creep lives of Ni-based single crystal superalloy through size effects and strengthening heterostructure γ/γʹ interfaces - Long Haibo; Zhao Yunsong; Zhao Junbo; Yuan Xiaoyi; Fan Hao; Luo Yushi; Li Wei; An Zibing; Mao Shengcheng; Liu Gang; Han Xiaodong (National Science Open)
This study presents a design strategy to enhance the high-temperature creep resistance of Ni-based superalloys. This strategy focuses on two principles: (1) minimizing the dimensions of γ/γ′ interfaces and γ channels by reducing the size of the γ′ phase; (2) key alloy composition control to strengthen the heterostructure γ/γ′ interfaces. This strategy proved very effective by the designed three superalloys’ prolonged creep lives. An alloy exhibits ultra-long creep life by 388 h at 1100°C/137 MPa, which runs at the highest level among those alloys without Ru addition. With Ru addition, an alloy that lasted for 748 h with a creep strain of ~6% at 1110°C/137 MPa is developed. This study provides a new route of high-temperature creep lives through heterostructure interfacial design with size effects and key alloying elements.